Crop succession and split-application of nitrogen effects on common bean yield in short no-tillage system - Mingotte, F. L.C. [UNESP]; Jardim, C. A. [UNESP]; Coelho, A. P. [UNESP]; Yada, M. M. [UNESP]; Leal, F. T. [UNESP]; Souza, S. S. [UNESP]; Lemos, L. B. [UNESP]; Fornasieri Filho, D. [UNESP] (Cambridge University Press (CUP), 2021)
Evaluating the effects of crop successions in no-tillage system (NTS) is essential for the correct recommendation of agronomic practices, such as top-dressing nitrogen fertilization. The aim was to evaluate the effect of the crop succession and the splitting of top-dressing N fertilization on the agronomic performance and economic viability of common bean crop. The experiment was conducted in southeastern Brazil for two agricultural seasons in an area under NTS, using a split-plot in randomized complete block design. The plots represented three cropping successions (maize in sole crop, maize intercropped with Urochloa ruziziensis and U. ruziziensis in sole crop) and the subplots composed of ten combinations of splitting of top-dressing N, at the stages V3, V4 and R5 of the common bean crop. In relation to the single application of the N dose of 90 kg ha-1, the common bean had higher response as a function of the N splitting schemes adopted, regardless of the previous cropping succession. The cropping successions evaluated did not interfere with the seed yield of common bean as subsequent crop, even at the beginning of the establishment of NTS. To obtain higher seed yield and economic viability, the N dose of 90 kg ha-1 indicated for the crop must be split and applied among the phenological stages V3, V4 and R5.
Keywords: Economic viability; intercropping; Phaseolus vulgaris L.; seed yield; soil cultivation